Management of Ocular Allergy Itch With an Antihistamine-Releasing Contact Lens. Issue 6 (June 2019) - Pall, Brian; Gomes, Paul; Yi, Frank; Torkildsen, Gail
Abstract : Purpose: A contact lens (CL)-based drug delivery system for therapeutic delivery of the antihistamine ketotifen was tested in 2 parallel, conjunctival allergen challenge-based trials. Methods: Both trials employed the same multicenter, randomized, placebo-controlled protocol. Test lenses were etafilcon A with 0.019 mg ketotifen; control lenses were etafilcon A with no added drug. Subjects were randomized into 3 treatment groups. Group 1 received test lens in one eye and control lens in the contralateral eye; the eye chosen to receive test lens was randomly selected in a 1:1 ratio. Group 2 received test lenses bilaterally, and group 3 received control lenses bilaterally. Allergen challenges were conducted on 2 separate visits: following lens insertion, the subjects were challenged at 15 minutes (to test onset) and 12 hours (to test duration). The primary endpoint was ocular itching measured using a 0 to 4 scale with half-unit steps. Secondary endpoints included ciliary, conjunctival, and episcleral hyperemia. Results: The mean itching scores were lower for eyes wearing the test lens as compared to those that received control lenses, indicating that the test lens effectively reduced allergic responses. Mean differences in itching were statistically and clinically significant (mean score difference ≥ 1) at both onset and duration for both trials. Conclusions: This large-scale assessment (n = 244) is the first demonstration of efficacy for CL delivery of a therapeutic for ocular allergy. Results are comparable to direct topical drug delivery and suggest that the lens/ketotifen combination can provide a means of simultaneous vision correction and treatment for CL wearers with ocular allergies. Abstract : Supplemental Digital Content is Available in the Text.